An overlapping phenotype of Osteogenesis imperfecta and Ehlers–Danlos syndrome due to a heterozygous mutation in COL1A1 and biallelic missense variants in TNXB identified by whole exome sequencing. Issue 4 (22nd January 2016) - Mackenroth, Luisa; Fischer‐Zirnsak, Björn; Egerer, Johannes; Hecht, Jochen; Kallinich, Tilmann; Stenzel, Werner; Spors, Birgit; von Moers, Arpad; Mundlos, Stefan; Kornak, Uwe; Gerhold, Kerstin; Horn, Denise
Abstract : Osteogenesis imperfecta (OI) and Ehlers–Danlos syndrome (EDS) are variable genetic disorders that overlap in different ways [Cole 1993; Grahame 1999]. Here, we describe a boy presenting with severe muscular hypotonia, multiple fractures, and joint hyperflexibility, features that are compatible with mild OI and hypermobility type EDS, respectively. By whole exome sequencing, we identified both a COL1A1 mutation (c.4006‐1G > A) inherited from the patient's mildly affected mother and biallelic missense variants in TNXB (p.Val1213Ile, p.Gly2592Ser). Analysis of cDNA showed that the COL1A1 splice site mutation led to intron retention causing a frameshift (p.Phe1336Valfs*72). Type 1 collagen secretion by the patient's skin fibroblasts was reduced. Immunostaining of a muscle biopsy obtained from the patient revealed a clear reduction of tenascin‐X in the extracellular matrix compared to a healthy control. These findings imply that the combination of the COL1A1 mutation with the TNXB variants might cause the patient's unique phenotype. © 2016 Wiley Periodicals, Inc.